Performance of Bus Operation Officers 1 at PT Transportasi Jakarta In Digital Era: Do The Work In-volvement, Loyalty, and Team Cooperation Matter? - Agus Faisal; Besar Agung Martono (Syntax Literate, 2022)
Transportation is one of the people's needs in community activities in the digital era, especially in Jakarta. One of the public transport available is Transjakarta, which is operated by PT Transportasi Jakarta. This study aims to determine the performance that is affected by the problem of bus operation officers who lack the initiative to involve themselves in the task. There is still no close cooperation between various lines in completing the work. In this study, the population was bus operations officer 1 PT Transportasi Jakarta, as many as 420 people. The sample used in this study was 200 samples with a significance of 5% with a simple random sampling method. Statistical multiple regression analysis was used to measure the effect of work involvement, work loyalty and teamwork on the performance of operator officers at PT Transportasi Jakarta. The results of the partial study for work involvement have no effect on performance, while work loyalty and teamwork have an effect on performance. Meanwhile, simultaneously (simultaneously) work involvement, work loyalty and teamwork will affect performance with a coefficient of determination of 68.1%, while 31.9% of other variables are not included in this study. This research is expected for officers to increase loyalty along with increase teamwork. For further researchers to add other variables so that the results obtained are more realistic. For PT Transportasi Jakarta to immediately change the performance appraisal component which has been emphasizing group values to personal-oriented values.